If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -12x = 0 Combine like terms: 11x + -12x = -1x -1x = 0 Solving -1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-1'. x = 0 Simplifying x = 0
| 300=x-(x*0.2) | | x^2+x+200=0 | | x^2+x+200=1 | | 250=x-(x*0.2) | | 250=x-(x*0.25) | | 1000=x-(x*0.2) | | 1800=x-(x*0.2) | | 1200=x-(x*0.25) | | -12+y=8 | | 2000=x-(x*0.25) | | 2000=x-(x*0.3) | | 2-3(4)=-2 | | 4-3(2)=-2 | | 2-3(2)=-2 | | 4-3(0)=-2 | | 0-3(4)=-2 | | 400=x-(x*0.2) | | 1400=x-(x*0.2) | | 350=x-(x*0.2) | | 350=x-(x*0.25) | | 0.2(-5)+2(0.5)=0 | | 1.72g-11=0.18 | | -5-4(0.5)=-7 | | 300=x-(x*0.25) | | 300=x-(x*0.3) | | 200=x-(x*0.2) | | 200=x-(x*0.25) | | 200=x-(x*0.3) | | 5(7x-3)= | | 500=x-(x*0.2) | | 1200=x-(x*0.2) | | 36*6(2+2+2)= |